217k views
3 votes
Given the Question below which of the following shows the quadratic formula correctly applied?

Given the Question below which of the following shows the quadratic formula correctly-example-1
User Yuriks
by
5.3k points

1 Answer

1 vote

ANSWER

D.


x = \frac{ - ( - 9 )\pm \sqrt{ {( - 9)}^(2) - 4(2)(4)} }{2(2)}

Step-by-step explanation

The given equation is


2 {x}^(2) - 9x + 4 = 0

When we compare this to:


a{x}^(2) + bx + c = 0

we have a=2, b=-9, and c=4.

The quadratic formula is given by,


x = \frac{ - b \pm \sqrt{ {b}^(2) - 4ac} }{2a}

We substitute the values into the formula to get,


x = \frac{ - ( - 9 )\pm \sqrt{ {( - 9)}^(2) - 4(2)(4)} }{2(2)}

The correct choice is D

User Mkutyba
by
4.4k points